The crime book - Hogan, Shanna; Kerrigan, Michael 1959-; Mellor, Lee 1982-; Morris, Rebecca T.; James, Peter (Big ideas simply explained, 2017)
Explores the cases of over one hundred notorious crimes and criminals from world history, covering bandits, arsonists, hucksters, white collar criminals, organized crime, kidnappers, extortionists, and murderers.